2015
DOI: 10.1179/2045772315y.0000000011
|View full text |Cite
|
Sign up to set email alerts
|

An unresolved relationship: the relationship between lesion severity and neurogenic bladder in patients with spinal cord injury

Abstract: Objectives: We aimed to investigate the relationship between the severity of the spinal lesion and urodynamic findings, bladder drainage method at discharge, and incidence of renal calculi in patients with spinal cord injury (SCI). Studydesign: Retrospective. Setting: In-patient rehabilitation unit of a tertiary research hospital. Methods: A total of 131 patients who were admitted to our clinic with a diagnosis of SCI and placed into a rehabilitation program were included in the study. The severity of the lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The higher prevalence of individuals with complete SCI admitted to the 3-day checkup program could be because the program focuses on neurogenic bladder management and urodynamic study. Individuals with complete SCI have more difficulty managing the bladder drainage method [22]. Four definitions of MetS given by the IDF, AHA/NHLBI, NCEP-ATP III, and WHO criteria are commonly used in studies and clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…The higher prevalence of individuals with complete SCI admitted to the 3-day checkup program could be because the program focuses on neurogenic bladder management and urodynamic study. Individuals with complete SCI have more difficulty managing the bladder drainage method [22]. Four definitions of MetS given by the IDF, AHA/NHLBI, NCEP-ATP III, and WHO criteria are commonly used in studies and clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies disregarded the course of the disease (18); other studies did not distinguish between suprasacral and subsacral injuries (8,9), or between complete and incomplete injuries (2,5,6,8,19). A retrospective study (20) compared urodynamics between suprasacral complete and incomplete SCI in 131 patients. The results showed that DO accounted for 30.6% of complete SCI, 41.3% were with incomplete SCI; low BC accounted for 54.1% of complete SCI, 56.5% of incomplete SCI, and bladder feeling absent accounted for 76.5% of complete SCI.…”
Section: Findings In the Context Of Existing Evidencementioning
confidence: 99%
“…They found no significant difference between the patients with complete and incomplete injuries in terms of age, sex, disease duration, detrusor hyperactivity and compliance; the bladder drainage method was found to show a significant change according to the severity of the lesion. They concluded that the urodynamic examination is required in each patient with SCI as the severity of the lesion is not sufficient to determine the bladder type, and patients with complete and incomplete injuries should be monitored with the same sensitivity in terms of complications [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, suprasacral lesions lead to detrusor overactivity and detrusor sphincter dyssynergia, whereby sacral SCI results in detrusor areflexia (and often increased bladder compliance) related to lower motor neuron lesions [ 17 ]. In a retrospective review of 316 patient records, Weld and Dmochowski tried to investigate the associations between the radiographically determined level of injury and urodynamic findings.…”
Section: Discussionmentioning
confidence: 99%